Penerapan metode pembelajaran peta konsep untuk meningkatkan kemampuan berpikir kritis dan kemampuan berpikir kreatif - Zulkarnain, Ali Iskandar (Jurnal Studi Agama dan Masyarakat, 2013)
The success of the learning process is influenced by various factors, one of which is a method of learning such as teaching methods appropriate concept map and used in accordance with the proportions. Also, critical thinking and creative thinking of students participate in providing considerable influence on academic achievement. The three aspects of both methods of learning concept map and critical thinking and creative thinking of students is less teacher attention so that learning is less fun. This study aims to find out how much the application of concept maps method can improve the ability of critical thinking and creative thinking of students in elementary social studies learning. To find out the answer to the problem in this study, the researcher who seeks information in the field of data processing based on data obtained can be explained that, the application of the method can improve the concept map ability critical thinking and creative thinking of students in primary school.Based on these results, it can be argued that the application of learning methods suggestion concept map can be used by teachers as one of the alternative methods of teaching social studies in primary school, specifically, on the subject of the economy and society can be used by other researchers to look at aspects of upgrading skills or skills other scientific as critical thinking and creative thinking of students.Â